2017
DOI: 10.1021/acsinfecdis.7b00129
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the Development of a Thiol-Based Broad-Spectrum Inhibitor for Metallo-β-Lactamases

Abstract: Pathogens, expressing metallo-β-lactamases (MBLs), become resistant against most β-lactam antibiotics. Besides the dragging search for new antibiotics, development of MBL inhibitors would be an alternative weapon against resistant bacterial pathogens. Inhibition of resistance enzymes could restore the antibacterial activity of β-lactams. Various approaches to MBL inhibitors are described; among others, the promising motif of a zinc coordinating thiol moiety is very popular. Nevertheless, since the first report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 45 publications
(92 reference statements)
4
43
0
Order By: Relevance
“…Dependent on L‐ or D‐ configuration of the proline moiety, the carboxyl group is facing a different side of the binding pocket and in the L1‐D‐captopril complex (2FU8), the carboxyl oxygen makes a hydrogen bond to OG of Ser223. The binding site of L1 (or other MLB) can accommodate various forms of a captopril molecule suggesting utilizable room to introduce derivatives for higher selectivity and affinity . The L1 structures are quite similar and all inter‐metal distances in the structures are around 3.7–3.8 Å.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dependent on L‐ or D‐ configuration of the proline moiety, the carboxyl group is facing a different side of the binding pocket and in the L1‐D‐captopril complex (2FU8), the carboxyl oxygen makes a hydrogen bond to OG of Ser223. The binding site of L1 (or other MLB) can accommodate various forms of a captopril molecule suggesting utilizable room to introduce derivatives for higher selectivity and affinity . The L1 structures are quite similar and all inter‐metal distances in the structures are around 3.7–3.8 Å.…”
Section: Resultsmentioning
confidence: 99%
“…The binding site of L1 (or other MLB) can accommodate various forms of a captopril molecule suggesting utilizable room to introduce derivatives for higher selectivity and affinity. 20,47 The L1 structures are quite similar and all inter-metal distances in the structures are around 3.7-3.8 Å.…”
Section: Structure Of L1-captoprilmentioning
confidence: 88%
“…Similar strategy has been used to discover thiorphan, tiopronin, and dimercaprol (Figure .8–10), which have the ability to inhibit NDM‐1, VIM‐1, and IMP‐7. Recently, some thiol‐based MBL inhibitors have been reported (Arjomandi et al., ; Büttner et al., ; Liu, Jing et al., ), including a series of amino acid‐derived thiol inhibitors reported by Arjomandi, in which the most potent compound of L‐tyrosine showed competitive inhibition with a Ki of 86 nM (Figure .11) (Arjomandi et al., ).…”
Section: Progress In Designing Metallo‐β‐lactamase Inhibitorsmentioning
confidence: 99%
“…7 For instance, thiomandelic acid and 2-mercapto-5-phenylpentanoic acid were discovered as a broad-spectrum inhibitor for MBLs where Cd-NMR studies demonstrated that the sulphur atom of the compound intercalates the metal ions within the active site and displaces the bridging water molecule that is essential for the MBL hydrolase activity. Further potent thiol containing compound reported with good IC50 by B€ uttner et al 42 The other potent thiol carboxylic acid compounds, bisthiazolidines, reported by Gonz alez et al 43 with Ki values in a range of 7-19 mM against NDM-1. The co-crystallised enzyme/ inhibitors of these compounds demonstrated that the sulphur atom of the mercaptomethyl group is positioned nearly equidistant between the two zinc ions, displacing the bridging water/ hydroxide molecule that is proposed to be the attacking nucleophile, but with little impact on the Zn1 À Zn2 distance.…”
Section: Introductionmentioning
confidence: 97%